1973
DOI: 10.1002/jsfa.2740240610
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of unripe (green) and ripe plantain (musa paradisiaca)

Abstract: The proximate chemical composition, the carbohydrate constituents and the amino acid make-up of green and ripe plantain were determined. The quantity of total sugars considerably increased during ripening from 3.0 to 31.6% in the peel and from 1.3 to 17.3 % in the pulp while starch concentration decreased from 50 to 35 % and from 83 to 66% in the skin and the pulp, respectively. The skin was richer in cellulose (10%) and hemicellulose (13 %) than the pulp which had 1.4 % cellulose and 1.3 % hemicellulose. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
43
1
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 7 publications
12
43
1
1
Order By: Relevance
“…Ladele, et al (1984) had reported that the moisture content of banana increased during storage, while the moisture content of ripe banana is higher that of the unripe fruit (Ketiku, 1973). Increase in crude fibre content was observed as from the 5th day.…”
Section: Discussionmentioning
confidence: 84%
“…Ladele, et al (1984) had reported that the moisture content of banana increased during storage, while the moisture content of ripe banana is higher that of the unripe fruit (Ketiku, 1973). Increase in crude fibre content was observed as from the 5th day.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, higher initial moisture content in food resulted in a higher drying rate, as expected. This led to a rapid decrease in moisture content in the fruit, and resulted in the same drying time for both January and March samples at The influence of maturity of banana on drying kinetics: There have been reports of changes in structure (intercellular space, cell wall) (Charles et al 1973;Marriot 1980;Prabha and Bhagyalakshimi 1998), permeability of membrane, chemical composition (including starch, sugar and water) (Ketiku 1973;Wills et al 1984;Ni et al 1993;Prabha and Bhagyalakshimi 1998) between green and ripe banana. It was therefore of interest to investigate the drying kinetics of banana of different maturity.…”
Section: The Influence Of Sample Thickness On Kinetics Of Drying Bananamentioning
confidence: 99%
“…The use of plantain and banana pulp and peel combination in wine manufacturing has been reported Full ReseachArticle (Adeniji, 1995;Berry, 1992). Rahman (1963) reported on the use of whole plantain fruit, consisting of both pulp and peel in flour production, while the peels and trunk are utilised for various agricultural purposes (Ketiku, 1973;Ankrah, 1974). In Nigeria, Cameroon, Cote d'Ivoire and other plantain producing countries in Africa, the entire fruit or pulps of unripe or half-ripe plantain are roasted on heated charcoal.…”
Section: Introductionmentioning
confidence: 99%